2009
DOI: 10.1007/s00209-009-0657-x
|View full text |Cite
|
Sign up to set email alerts
|

Homeomorphisms of the annulus with a transitive lift

Abstract: Let f be a homeomorphism of the closed annulus A that preserves the orientation, the boundary components and that has a liftf to the infinite stripà which is transitive. We show that, if the rotation numbers of both boundary components of A are strictly positive, then there exists a closed nonempty unbounded setif p 1 is the projection on the first coordinate ofÃ, then there exists d > 0 such that, for anỹIn particular, using a result of Franks, we show that the rotation set of any homeomorphism of the annulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…The work [4] suggests this is also true C 1 generically. In [1] it is shown that, if g is a homeomorphism of the closed annulus whose lift g to the strip R × [0, 1] is transitive, and if there are no fixed points in the boundary of the annulus, then 0 is in the interior of the rotation interval of g. Some of the ideas presented in this paper follow from that paper.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The work [4] suggests this is also true C 1 generically. In [1] it is shown that, if g is a homeomorphism of the closed annulus whose lift g to the strip R × [0, 1] is transitive, and if there are no fixed points in the boundary of the annulus, then 0 is in the interior of the rotation interval of g. Some of the ideas presented in this paper follow from that paper.…”
Section: Introductionmentioning
confidence: 84%
“…First, note that the orbit of x T is not bounded in any direction, and as such If tg(θ) is rational, then the result follows from Proposition 5 by taking v ∈ Z 2 perpendicular to e θ , since each of the points x T + iv, i ∈ Z needs to be in a different connected component of O 1 .…”
Section: Proposition 4 Ifx Is a Point Of O 1 And I J Are Integers Smentioning
confidence: 99%
See 2 more Smart Citations
“…In this subsection we define the set B − , introduced in [1], that will play an important role in the proof of our theorem. Although much of what is done in this subsection can be found in [1], for completeness sake we present all results needed with proofs.…”
Section: The Set Bmentioning
confidence: 99%